Is There a Link Between Creativity and Multiculturalism in Education? - OGRUTAN Petre Lucian; MACHIDON Alina Luminita; DINU Alexandru (TEM Journal, 2019)
This paper presents a few initiatives of developing Electronics engineering students’ creativity and the achieved outcomes. After implementing these initiatives, a student group including students of different nationalities, distinguished themselves by their outstanding achievements in comparison with other three groups of students of identical nationalities. This paper emphasizes some aspects of intercultural cooperation and proposes the hypothesis of this cooperation as the driving force behind the development of student creativity.